Nutritive value of pastures of Cynodon mixed with forage peanut in southwestern Paraná State - Magnos Fernando Ziech; Clair Jorge Olivo; Ana Regina Dahlem Ziech; Wagner Paris; Carlos Alberto Agnolin; Gilmar Roberto Meinerz (Acta Scientiarum. Animal Sciences, 2015)
This study evaluated the nutritive value of pastures of Coastcross-1 and Tifton 85 mixed with increasing inclusion of forage peanut (0, 25, 50, 75% occupancy area), subjected to cuts, over two study years in Southwestern Paraná State. The experimental design was factorial (three factors) distributed in randomized block. The factors were cultivars (2), the occupancy area of forage peanut (4) and seasons of cuts (5), with three replications. It was evaluated the percentage of crude protein, neutral detergent fiber and in vitro digestibility of dry matter of leaf blades, stem + sheath of grasses and available forage mass of pastures. Values of crude protein ranged from 17.0 to 20.4% and from 16.8 to 19.3% for the forage mass available of Coastcross-1 and Tifton 85, respectively. Higher digestibility values were found at the beginning of evaluations. On average, the Coastcross-1 showed better nutritive value compared to Tifton 85, and, the inclusion of forage peanut increased crude protein content in leaf blades of grasses studied, in the second year after planted.